Vigilância digital e suas implicações no âmbito da educação: uma revisão sistemática da literatura - Sgoti, Rogério Ferreira (2024)
In the contemporary context of a digital culture already deeply rooted in current societies, this study aimed to analyze how the theme of "digital surveillance" has been addressed in the scientific literature in the Brazilian context, especially in its ramifications in the educational field. Thus, through an exploratory study with a qualitative-quantitative approach, enabled by the execution of a systematic literature review, the contexts of surveillance capitalism, algorithmic modulation, and data colonialism were analyzed in their influences in the field of education. In this sense, digitally vigilant practices carried out on networked digital platforms, owned by information technology mega corporations (big techs), have also been exercised in the educational context. This panorama, heavily impacted by the migration of pedagogical activities to online educational platforms caused by the Covid-19 pandemic, exposed the education sector to a market in which personal data and data from interactions on networked platforms are highly valuable. Through this study, it was possible to understand the phenomenon of digital surveillance based on scientific production in the national context. However, it was considered that the quantity of publications addressing the theme is still incipient, especially with its focus on education.